Innovation in the broadcasters' business model: A bibliometric and review approach - Esther Medina; Andres Mazaira; Elisa Alén (European Research on Management and Business Economics (ERMBE), 2022)
The aim of this paper is to relate innovation with the broadcasters' business model, by way of a bibliometric and review analysis. This comprises to study how they have incorporated the innovation and the effect of a disruptive innovation (as the Internet and other technologies) in their business model. To achieve these objectives a review of the scientific literature has been carried out, followed of an analysis in which obtained papers were classified according three dimensions: (i) Value Architecture Innovation, (ii) Value Offering Innovation and (iii) the Revenue Model Innovation. These dimensions are based on a reinterpretation of a previous classification which consider that business model innovation materialises with a change of the company that affects at least one out of the three mentioned dimensions. In this way, a classification of the reviewed documents has been established based on these dimensions, showing that broadcasters have adopted a sustained business model innovation, with 48%, 44% and only 8%, respectively, in each dimension. By means of a scientific mapping of the keywords of the documents reviewed, a series of main and secondary topics have been established within each dimension, which have been analysed in terms of their contents and temporal evolution. It discusses the difficulties faced by broadcasters in adapting to the new audiovisual ecosystem. This study also argues that the Internet is one of the most disruptive innovations they have had to face and, therefore, in order to survive, they must take on this type of innovation to transform their business model.
Keywords: O320; 650; Internet; Mass media; Television; Traditional audiovisual media